COVID-19 and Sustainability in Higher Education : Reflective Review - Afzal Sayed Munna (Har Press Indonesia, 2021)
Sustainability is a lifestyle designed for permanence. Sustainability is the comparatively more uncomplicated idea, which can be explained in purely descriptive terms as any given system's capacity to exist and reproduce on a long-term basis. This study applied for the thoughtful review; the researcher collected data using secondary sources and used various peer-reviewed journal articles and various government and agency publications. The researcher also used personal reflection from the higher education practice. The measure of reflection explored the experimental research methods (primarily reflection) using literary forms. The development adds a value judgment by implying the desired evolution of human society. Sustainability in Higher Education calls us to new sets of relationships with our students, with each other, with what we learn, and with ourselves. In this thoughtful review, the researcher has attempted to reveal some common facts relating to COVID-19 and higher education sustainability.